The Social Survey of Merseyside - Carpenter, Niles (Quarterly Journal of Economics, 1935)
Journal Article The Social Survey of Merseyside Get access Niles Carpenter Niles Carpenter University of Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 4, August 1935, Pages 680–693, https://doi.org/10.2307/1885405 Published: 01 August 1935